Small intestinal hemorrhage in a patient with Neurofibromatosis type 1 - Guevara-Peralta, Katia Gesell (2023)
We present the case of a 32-year-old male patient with a history of Neurofibromatosis type 1, who presented with active small bowel bleeding, initially diagnosed by observing bleeding in ileoscopy, presenting with hemodynamic instability, abdominal angiotomography was performed, identifying a mass with contrast enhancement and active bleeding at the middle jejunum level, for which an angiography with arterial embolization of the branch that supplies said area is performed. With the patient stable, a double-balloon antegrade enteroscopy was performed, observing a subepithelial, ulcerated lesion, endoscopic tattooing was performed and finally urgery was sent for resection by laparoscopy. The pathology study was compatible with a jejunal gastrointestinal stromal tumor (GIST).